ARTIFICIAL INTELLIGENCE IN EDUCATION: TRANSFORMING THE LEARNING EXPERIENCE - Nhuyen Yan Hoana (International Journal of Literature and Language Studies, 2026)
In the modern digital age, Artificial Intelligence (AI) has emerged as a transformative force across various sectors, and education is no exception. AI technologies are redefining teaching methodologies, personalizing the learning experience, automating assessments, and enabling real-time feedback. This article explores the multifaceted impact of AI on education, emphasizing how intelligent systems enhance student performance, aid teachers, and support inclusive learning environments. The paper also critically analyzes ethical considerations, data privacy issues, and equity challenges in AI implementation. As educational institutions globally adopt smart technologies, it becomes vital to assess not only the benefits but also the long-term implications of AI in learning ecosystems. Ultimately, the article advocates for a balanced, human-centered approach to ensure that technology enhances educational equity, quality, and sustainability.